Comparison between the impact of tenofovir alafenamide and that of abacavir on rapid kidney function decline: A retrospective observational study. Issue 4 (20th September 2022) - Hikasa, Shinichi; Shimabukuro, Shota; Hideta, Kyoko; Higasa, Satoshi; Sawada, Akihiro; Tokugawa, Tazuko; Tanaka, Kuniyoshi; Yanai, Mina; Kimura, Takeshi
Abstract: Objectives: To compare the impact of tenofovir alafenamide (TAF) on the slope of the estimated glomerular filtration rate (eGFR) with that of abacavir in Japanese patients living with HIV infection. Methods: The participants in this single‐centre, retrospective, observational study were Japanese patients with HIV infection who started antiretroviral therapy with TAF/emtricitabine or abacavir/lamivudine or were switched from tenofovir disoproxil fumarate/emtricitabine to TAF/emtricitabine or abacavir/lamivudine (anchor drugs remained constant) between January 2012 and December 2020. The eGFR slope was defined as the regression coefficient between eGFR and time. The study outcome was rapid kidney function decline (RKFD; eGFR slope < −5 mL/min/1.73 m 2 /year). The adjusted effect of TAF on the eGFR slope was compared with that of abacavir using multivariate logistic regression analysis. Results: The study included 184 patients (with 2835 eGFR data points). The median duration of exposure to TAF or abacavir was 2.6 years [interquartile range (IQR): 1.7–3.3], and the median eGFR slope was −4.1 mL/min/1.73 m 2 /year (IQR: −6.4 to −1.2). In all, 72 patients (39%) experienced RKFD. Patients receiving TAF were more likely to experience RKFD (adjusted odds ratio = 3.74) than those receiving abacavir. There was a significant independent association between baseline eGFR and RKFD. Conclusions: These findings suggest that renal function should be monitored carefully after the initiation of TAF in Japanese patients with HIV infection.